2018
DOI: 10.1089/lap.2018.0297
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Ventilation Patterns in Morbidly Obese Patients Undergoing Laparoscopic Bariatric Surgery

Abstract: The significant variation in TV per kg IBW as well as in PEEP values at our institution may reflect the lack of well-established guidelines for intraoperative ventilation. Many patients in this study received inappropriately large TVs (>8 mL/kg IBW), which may be due to calculation of TVs based on total body weight rather than IBW. Patients of shorter stature and higher body mass index appear to be at higher risk for ventilation with inappropriately large TVs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Perioperative patients may have healthy lungs; however, guidelines for ventilation settings might not be well-established and might cause ventilator-induced lung injury [183]. It is feasible to use EIT to individualize tidal volume and PEEP before surgery [184,185].…”
Section: Applications In Perioperative Patientsmentioning
confidence: 99%
“…Perioperative patients may have healthy lungs; however, guidelines for ventilation settings might not be well-established and might cause ventilator-induced lung injury [183]. It is feasible to use EIT to individualize tidal volume and PEEP before surgery [184,185].…”
Section: Applications In Perioperative Patientsmentioning
confidence: 99%
“…EIT generates cross-sectional images of the internal distribution of electrical impedance continuously at the bedside, which explains its high temporal resolution [ 42 , 43 ]. Poor posture means the solution for intrathoracic impedances may be unstable: small errors in voltage measurements disrupt reconstruction.…”
Section: Electrical Impedance Tomographymentioning
confidence: 99%
“…It has also been shown that in order to refine the measurements, the estimation of lung function from data obtained from the sixth intercostal space is more reliable than that obtained from the fourth intercostal space. Finally, a seated position is easier to tolerate by the subjects [ 42 ].…”
Section: Applications Of Eitmentioning
confidence: 99%